2020
DOI: 10.14744/nci.2020.70845
|View full text |Cite
|
Sign up to set email alerts
|

Associations between cytokine gene polymorphisms and rheumatoid arthritis in Turkish population

Abstract: OBJECTIVE: Various cytokine polymorphisms have been associated with genetic risk factors predisposing to Rheumatoid Arthritis (RA) in different populations. To predict the clinical outcome as well as response to therapy in RA, studies aimed to describe genetic markers. The present study aims to search for polymorphisms of 13 cytokine coding genes in the Eastern Black Sea Region of Turkey. METHODS: DNAs of 49 patients and 96 healthy bone marrow and kidney donors were iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Little is known about the genetic background of IL-2 in RA, but it was found that specific diplotypes, meaning the combination of haplotypes from both parents, in occurrence, the IL-2 TG:GG was positively associated with RA in the Turkish population [96]. Interestingly, the implication of this cytokine in joint-related pathologies seems to be dual and its use as a therapeutic target may be approached in a modulatory manner as contra-dictory data were addressed regarding this cytokine in this particular context.…”
Section: Micro-immunotherapy: a Multiple Immune-targeted Ultra-low-dose-based Strategy To Calm Chronic Inflammation In Ramentioning
confidence: 99%
“…Little is known about the genetic background of IL-2 in RA, but it was found that specific diplotypes, meaning the combination of haplotypes from both parents, in occurrence, the IL-2 TG:GG was positively associated with RA in the Turkish population [96]. Interestingly, the implication of this cytokine in joint-related pathologies seems to be dual and its use as a therapeutic target may be approached in a modulatory manner as contra-dictory data were addressed regarding this cytokine in this particular context.…”
Section: Micro-immunotherapy: a Multiple Immune-targeted Ultra-low-dose-based Strategy To Calm Chronic Inflammation In Ramentioning
confidence: 99%
“…The IL-2 TG:GG cytokine diplotype was found to be positively associated with RA in a study on Turkish individuals with the disease published in 2020. On the other hand, no meaningfully adverse link was found [32].…”
Section: Interleukine-2 Gene Polymorphismmentioning
confidence: 85%
“…The rs36215814 polymorphism was strongly related with a greater incidence of RA in both the dominant and additive genetic models. The IL-6 GG haplotype was positively related with RA, according to a study conducted in 2020 among Turkish patients with RA [32].…”
Section: Interleukine-6 Gene Polymorphismmentioning
confidence: 99%
“…The study of polymorphism in 108 early RA patients revealed the polymorphic IL-4 gene sequence located at 5q31-31 [29]. Furthermore, IL-4-590 promoter polymorphism was observed and was suggested as a genetic risk factor for the severity of RA [30][31][32][33]. IL-4R single-nucleotide polymorphism (SNP) is associated with radiographic progression in RA patients treated with methotrexate (MTX) monotherapy [34].…”
Section: Type 2 Immune Responses In Arthritismentioning
confidence: 99%